2005
DOI: 10.4049/jimmunol.174.6.3454
|View full text |Cite
|
Sign up to set email alerts
|

VH1–46 Is the Dominant Immunoglobulin Heavy Chain Gene Segment in Rotavirus-Specific Memory B Cells Expressing the Intestinal Homing Receptor α4β7

Abstract: Memory B cells expressing the intestinal homing marker α4β7 are important for protective immunity against human rotavirus (RV). It is not known whether the B cell repertoire of intestinal homing B cells differs from B cells of the systemic compartment. In this study, we analyzed the RV-specific VH and VL repertoire in human IgD− B cells expressing the intestinal homing marker α4β7. The mean frequency of RV-specific B cells in the systemic compartment of healthy adult subjects was 0.6% (range, 0.2–1.2). The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…We found that the proportion of RV VP6-specific B cells that are memory cells represents a lower frequency and a less frequently isotype-switch phenotype compared with the proportion of randomly selected B cells that are memory cells. This high proportion of naive B cells in virus-specific clones in the circulation during infection, even in adults who likely have a history of many previous RV infections, is curious and unexplained (14,15,17). We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We found that the proportion of RV VP6-specific B cells that are memory cells represents a lower frequency and a less frequently isotype-switch phenotype compared with the proportion of randomly selected B cells that are memory cells. This high proportion of naive B cells in virus-specific clones in the circulation during infection, even in adults who likely have a history of many previous RV infections, is curious and unexplained (14,15,17). We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17).…”
Section: Discussionmentioning
confidence: 70%
“…We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17). The Ab genes of RV-specific intestinal-homing memory (␣ 4 ␤ 7 ϩ IgD Ϫ ) B cells in particular are almost completely devoid of somatic mutations, even though they are isotype switched (17). Our previous studies, however, considered IgD ϩ -positive cells to be naive cells, whereas recent studies show that a third major subset of B cells exists within the unclass-switched IgD ϩ population (i.e., CD27 ϩ IgD ϩ cells) that are memory cells (18,19).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although there is no direct evidence of such a mechanism, several recent studies indicate the presence of repertoire-based regulatory mechanisms in circulating B-cell subsets. Despite the tendency of pathogen-specific antibody responses to exhibit biased germline gene repertoires, [16][17][18] the frequency of gene family use in naïve and memory subsets is remarkably consistent across individuals. 9,11 Further, alteration of this gene family homeostasis in the circulating B-cell repertoire is associated with disease states.…”
Section: Resultsmentioning
confidence: 99%